Functional Responses of Phytoplankton Assemblages to Watershed Land Use and Environmental Gradients - Du, Xue; Song, Dan; Ming, Kun; Yang, Jingshuang; Jin, Xing; Wang, Huibo; Liu, Hui; Wang, Le; Zhao, Chen; Huo, Tangbin (Frontiers in Ecology and Evolution, 2022)
Watershed land use changes have been identified as major threats to lake fauna, subsequently affecting ecosystem functioning. In this context, the functional-based approach was used to examine the effects of land use and environmental changes on phytoplankton communities in four selected lakes in Northeast China. We also identified the sensitive functional traits as indicators to environmental stressors. The integration of RLQ analysis with fourth-corner approach significantly identified five of 18 functional trait categories, including flagella, filamentous, unicellular, mixotrophic and chlorophyll c, as potential indicators to changes in watershed land use intensity and environmental gradients. Significant relationships between traits and land-use and water quality highlighted the consequential indirect impact of extensive agricultural and urban development on phytoplankton via allochthonous nutrient inputs and various contaminants. In addition, functional richness of phytoplankton assemblages generally increased along with surface area and forests but decreased along with intensive agricultural and urban land use, implying that functional homogenization may cause a reduction in ecosystem productivity and reliability to land use intensity. Given the superior performance of functional-based approach, our findings also highlighted the importance of application of both biological traits and functional diversity index in monitoring programs for lake ecosystems.